Financial Effect of a Drug Distribution Model Change on a Health System. Issue 6 (June 2017) - Turingan, Erin M.; Mekoba, Bijan C.; Eberwein, Samuel M.; Roberts, Patricia A.; Pappas, Ashley L.; Cruz, Jennifer L.; Amerine, Lindsey B.
Background: Drug manufacturers change distribution models based on patient safety and product integrity needs. These model changes can limit health-system access to medications, and the financial impact on health systems can be significant.Objective: The primary aim of this study was to determine the health-system financial impact of a manufacturer's change from open to limited distribution for bevacizumab (Avastin), rituximab (Rituxan), and trastuzumab (Herceptin). The secondary aim was to identify opportunities to shift administration to outpatient settings to support formulary change.Methods: To assess the financial impact on the health system, the cost minus discount was applied to total drug expenditure during a 1-year period after the distribution model change. The opportunity analysis was conducted for three institutions within the health system through chart review of each inpatient administration. Opportunity cost was the sum of the inpatient administration cost and outpatient administration margin.Results: The total drug expenditure for the study period was $26 427 263. By applying the cost minus discount, the financial effect of the distribution model change was $1 393 606. A total of 387 administrations were determined to be opportunities to be shifted to the outpatient setting. During the study period, the total opportunity cost was $1 766 049.Conclusion: Drug expenditure increased for the health system due to the drug distribution model change and loss of cost minus discount. The opportunity cost of shifting inpatient administrations could offset the increase in expenditure. It is recommended to restrict bevacizumab, rituximab, and trastuzumab through Pharmacy & Therapeutics Committees to outpatient use where clinically appropriate.